PROFESSIONAL IDENTITY OF NURSES IN THE MENTAL HEALTH FIELD: AN INTEGRATIVE REVIEW - Oliveira, Tâmara da Cruz Piedade; Silva, Ingredy Nayara Chiacchio; Santos, Sélton Diniz dos; Almeida, Deybson Borba de; Silva, Gilberto Tadeu Reis da (Cogitare Enfermagem, 2023)
Objective: to analyze the production of knowledge in the scientific literature on the constitution of professional identity in nurses working in the field of mental health. Method: integrative literature review through the Virtual Health Library portal in four databases: Lilacs, Scielo, PubMed and BDENF. The eligibility criteria were full original articles published from 2017-2022 in English, Portuguese, or Spanish. Results: the sample was composed of 18 studies grouped into two thematic categories. The results are about the (in)definitions of the work process of nurses working in the mental health field, and about the fragmentation of care and its implications for the constitution of this professional identity. Conclusion: nurses play diversified roles in their daily work, which contributes to an insufficient understanding of their scope of attributions and directly impacts the perception of their professional identity.